Pengaruh Perilaku Konsumen terhadap Keputusan Pembelian pada Urban Cafe (Coffee&Eatery) di Kecamatan Garut Kota - Nufika Shilhan Zein; Asep Permadi Gumelar; Fitri Awaliyah; Muhamad Nu’man Adinasa (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2023)
Urban Cafe is a coffee cafe located in Garut Kota District, from January 2021 to February 2022 the number of visitors has increased and decreased. This study aims to determine the influence of social, psychological, and personal factors on purchasing decisions, and to determine the most influential factors on purchasing decisions at Urban Cafe. The research method used is descriptive quantitative research. The processed data is the result of distributing questionnaires to 76 Urban Cafe visitors as respondents. The data analysis technique used in this study is multiple linear regression. To explain the description of research related to the hypothesis using analysis: Validity Test, Reliability Test, Classical Assumption Test, Normality Test, Heteroscedasticity Test, Autocorrelation Test, Multicollinearity Test, Hypothesis Test, T Test, F Test, Determination (R2). Based on the results of data analysis for the significance test T test shows that social variables (X1), personal (X2) partially have a positive and significant effect on the decision to purchase food and drinks at Urban Cafe, and for psychological variables (X3) have an effect but not significant, and F test results personal factor is the variable that dominantly influences purchasing decisions with a value of 20.356.